2015
DOI: 10.5141/ecoenv.2015.043
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for the relationship of environmental factors and vegetation structure at natural streamside valley and riparian forest in South Korea

Abstract: We classified the streamside plant community by phyto-sociological method and analyzed the relationship between environment factors and vegetation structure by using the classification and ordination method. We found that twenty one plant communities were classified according to dominant species at the natural streamside valley forest with surveying the 65 quadrats (10 m × 10 m). From the survey results, the hardwood plant communities were classified as streamside valley forest and the softwood plant communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Density and variability of weed species also depend on the inconstancy of both anthropogenic and ecological variables [15]. The essential properties of soil i.e., its pH, fertility, structure, and texture as well as crop rotation, farming practices and availability of moisture strongly impact the weed count and its heterogeneity.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Density and variability of weed species also depend on the inconstancy of both anthropogenic and ecological variables [15]. The essential properties of soil i.e., its pH, fertility, structure, and texture as well as crop rotation, farming practices and availability of moisture strongly impact the weed count and its heterogeneity.…”
Section: Plos Onementioning
confidence: 99%
“…But until now, the precise weed data correlated to various soil properties is limited, even though soil sensing approaches ensure soil data evaluations at high spatial resolution. Variability in the weed community structure and its distribution is chiefly influenced by various ecological drivers including crop type and its sustainability, farm management practices, physico-chemistry of the soil, seasonality, and urbanization [15].…”
Section: Introductionmentioning
confidence: 99%
“…(2001); Walther et al. (2002); Andreasen and Skovgaard (2009); Hanzlik and Gerowitt (2011); Cho et al. (2015) and Mahgoub (2017); revealed that the significance of local site characteristics such as abiotic factors (soil and climate) and management practices for the occurrence of single species, community composition and species richness, are profound.…”
Section: Introductionmentioning
confidence: 99%
“…TWINSPAN, modified using an indicator species analysis, is capable of both quadrat and species classification, based on a reciprocal averaging axis [28]. In the present study, WinTWINS 2.3 software was used to perform TWINSPAN quantitative classification based on the importance value matrix and environmental factor matrix of vegetation species in typical quadrats, as well as the results of the 4th classification [29,30].…”
Section: Twinspan Quantitative Classificationmentioning
confidence: 99%
“…TWINSPAN quantitative classification is based on indicator species. Generally, five main dominant species are selected as important indicator species to objectively classify vegetation communities using TWINSPAN [28,31]. The method of DCA ordination was proposed by Hill and Gauch after research based on a correspondence analysis [34].…”
Section: Twinspan Quantity Classification and Dca Ordination Featuresmentioning
confidence: 99%